Survei Implementasi Kurikulum Merdeka Pada Pembelajaran PJOK SMP Se Kabupaten Bojonegoro - Iqbal Akbar Albani; Mu'arifin Mu'arifin (Universitas Palangka Raya, 2023)
The independent curriculum provides freedom to export students' abilities and interests. Changes in government policy on the education system have a good and bad impact on the quality of education. This study aims to find out how the implementation of the independent curriculum by looking at the teacher's understanding and the problems faced. This research method uses quantitative and qualitative. The research instrument used questionnaires and interviews. With the research subject of junior high school teachers in Bojonegoro Regency with purposive sampling techniques with the first criterion, the school implemented an independent curriculum. Second, PJOK teachers are linear graduates. Quantitative research data is analyzed in the form of percentages and qualitative research data is reduced then analyzed and presented according to reality in the field. The average percentage result of teacher perception on independent curriculum understanding is 73% and it can be concluded that teachers have high understanding based on percentage results. Then the results of the study revealed that almost 90% of junior high schools in Bojonegoro have implemented an independent curriculum. The highest result of the problems faced by teachers is that at the learning planning stage 57% experience problems at the Difficulty in stringing together sentences of operational and concrete learning objectives, at the stage of implementation 40% have difficulty designing learning based on the needs of students Difficulty designing projects Strengthening the Profile of Pancasila in learning, at the monitoring stage 48.6% experience Difficulty analyzing student conditions for assessment purposes and at stages 45.7% Difficulty developing questions from the questions provided.